Prevalence and risk factors of hearing loss and otological symptoms among Sickle Cell Disease patients in Saudi Arabia: a single center experience - Alabssi, Haila; Alfares, Maiadah; AL Mulhim, Noura; Latif, Rabia; Rafique , Nazish; Almulhim, Nouf; Alismail, Maram; Algheryafi , Samar; Bokhari, Danah; Alzayyat, Remah; AlShaikh Sulaiman , Amal; Alwaheed, Abrar (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Sickle Cell Disease (SCD) is a genetic hematological disorder associated with various complications, including sensorineural hearing loss (SNHL). However, the prevalence and risk factors of SNHL among SCD patients remain unclear. The aim of the study is to determine the prevalence and risk factors of sensorineural hearing loss along with otological manifestations in SCD patients; to compare the findings between mild-moderate versus severe SCD patients. Research design and methods: A cross-sectional study was conducted between December 2022 and March 2023 at King Fahd University Hospital in Al Khobar. The study included fifty-four SCD patients (18-45 years old) who were receiving follow-up care. Participants underwent comprehensive audiological assessments; The Otology Questionnaire Amsterdam and clinical parameters were used to assess hearing in the patients. Results: Twelve patients (22.2%) had hearing loss on pure tone audiometry. Hearing loss risk factors in SCD patients were not statistically significant in our sample (P > 0.05). The Otology Questionnaire Amsterdam impact domain score and most of the complaints apart from ear itching and loss of taste showed a statistically significant correlation with SCD severity (P < 0.05). Conclusions: Sensorineural hearing loss is not uncommon in patients with sickle cell disease. Our study did not demonstrate any significant risk factors for hearing loss. However, the severity of various otological symptoms correlated significantly with SCD disease severity. Screening for ear-related complaints is therefore encouraged during patient encounters.